A REVIEW OF ISLAMIC LAW ON PEOPLE WHO WORK IN THE BANKING SECTOR - Adi, Baihaqy Prianto (Pondok Pesantren Modern Islam Assalaam, 2023)
This study aims to examine more deeply the law of people working in the banking sector, because it is still being debated for now, as it is clear that the world of conventional banking cannot be separated from interest and absolute interest in the category of usury, therefore interacting with usury is unlawful. Then what is the current view of Islamic law regarding people who work in banking. The method used in this study is library research which is qualitative in nature, data was collected using the documentary method, the method of analyzing descriptive analytic data. The results of this study indicate that the law of usury is absolutely forbidden, but for now not all activities in banking contain elements of usury, for this reason there is an opinion that it is permissible to work in the banking sector with the support of someone in an emergency and emergency situation because they cannot get another job that is capable meet life’s needs as the opinion of Yusuf Qardhawi. While the majority of scholars forbid it as QS. Al-Maidah verse 2, which works in the banking sector is included in the category of helping in committing sins and committing offenses